INVESTIGATING AN ONLINE ENGLISH TEACHING IN AN INDONESIAN ELEMENTARY SCHOOL - Alfin Maghfiroh; Mukminatus Zuhriyah (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
Investigation of online English learning is implemented in Jombang. This study aims to determine the online learning process during the Covid-19 pandemic. Some of the inhibiting factors in the implementation of online learning are the lack of parental support, few students who have smartphones, student laziness and lack of motivation to learn, difficult to control and evaluate student assignments. While the supporting factors obtained by the teacher when carrying out online learning are more online learning materials, time and place efficiency, and learning materials can be stored safely on smartphones. This research was conducted with descriptive methods and data collection techniques by interviewing English teachers. The result of the research is the implementation of online English learning in one of the elementary schools in Jombang, using the WhatsApp application as an online learning medium. Submission of materials and assignments is done through the WhatsApp group media.